2017
DOI: 10.1016/j.jmbbm.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of cross-linked gellan gum and retrograded starch blend hydrogels for drug delivery applications

Abstract: The retrogradation of high amylose starch (5% or 10%), by isothermal cycles at 4°C (method 1) or by alternating thermal cycles (method 2) was efficient and promoted important structural modifications. Hydrogels of gellan gum and starch retrograded blends, containing or not ketoprofen, were prepared by ionic and dual cross-linking, at different concentrations of polymer and cross-linkers, and characterized by texture and rheological analysis, X-ray diffraction and morphological analysis. The ionic cross-linking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(28 citation statements)
references
References 97 publications
0
22
0
1
Order By: Relevance
“…This corroborates the rheological data that demonstrated that the FPC formulation is highly elastic. de Oliveira Cardoso et al (66) also demonstrated that more elastic formulations further control drug release (68).…”
Section: Resultsmentioning
confidence: 98%
“…This corroborates the rheological data that demonstrated that the FPC formulation is highly elastic. de Oliveira Cardoso et al (66) also demonstrated that more elastic formulations further control drug release (68).…”
Section: Resultsmentioning
confidence: 98%
“…The clay promoted interactions between the polymer and the clay, increasing the material’s elastic modulus and producing a stronger and more stable gel [ 92 ]. However, the use of these hydrogels is limited to certain tissues because of their mechanical properties; although, these can be increased by blending GG with other compounds such as starch [ 93 ].…”
Section: Exopolysaccharides For Producing Ddssmentioning
confidence: 99%
“…Hardness: was obtained as the maximum force required to achieve a deformation or defined as maximum peak force in the first cycle of compression [23,[39][40][41].…”
Section: Texture Profile Analysis (Tpa)mentioning
confidence: 99%